2022
DOI: 10.34172/jrip.2022.31933
|View full text |Cite
|
Sign up to set email alerts
|

The effect of olive leaf use on blood pressure; A systematic review and meta-analysis

Abstract: Context: Hypertension has been identified as the world’s third leading cause of death. Due to their cost-effectiveness and lack of adverse effects compared to antihypertensive medications, medicinal plants have gained popularity in most countries. The olive leaf is one of these plants. As a result, the purpose of the current systematic review and meta-analysis was to determine the effect of olive leaf consumption on systolic and diastolic blood pressure. Evidence acquisition: The following domestic and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…7 Similar results were reported by Fatahian et al in a metaanalysis of five human studies (n = 145 participants), SBP and DBP being found to decrease by 0.87 and 0.39 mmHg, respectively, after olive leaf consumption. 24 In contrast, another metaanalysis found a reduction only in SBP of 11.5 mmHg after daily supplementation with 500 mg of OLE, but no significant effect on either SBP or DBP was observed after administering higher daily doses (1000 mg). 17 The possibility that OLE is more beneficial in hypertensive patients, as concluded by Razmpoosh et al, 7 indicates a mechanism of action that affects blood pressure together with other cardiovascular risk factors.…”
Section: Olive Pomace Oilmentioning
confidence: 95%
See 3 more Smart Citations
“…7 Similar results were reported by Fatahian et al in a metaanalysis of five human studies (n = 145 participants), SBP and DBP being found to decrease by 0.87 and 0.39 mmHg, respectively, after olive leaf consumption. 24 In contrast, another metaanalysis found a reduction only in SBP of 11.5 mmHg after daily supplementation with 500 mg of OLE, but no significant effect on either SBP or DBP was observed after administering higher daily doses (1000 mg). 17 The possibility that OLE is more beneficial in hypertensive patients, as concluded by Razmpoosh et al, 7 indicates a mechanism of action that affects blood pressure together with other cardiovascular risk factors.…”
Section: Olive Pomace Oilmentioning
confidence: 95%
“…In addition, possible interactions between different bioactive compounds in the by-products have not been investigated. A further limitation, as highlighted by Razmpoosh et al and Fatahian et al, 7,24 is that most of the clinical trials covered in this review had short intervention periods, typically 4-8 weeks, which may not be sufficient to assess long-term effects on cardiometabolic and inflammatory markers, especially in healthy subjects.…”
Section: Olive Pomace Oilmentioning
confidence: 98%
See 2 more Smart Citations